2017
DOI: 10.17533/udea.rccp.v30n3a06
|View full text |Cite
|
Sign up to set email alerts
|

Serum cortisol concentration in the Colombian Creole Horse

Abstract: Concentración del cortisol sérico en el caballo criollo colombiano Concentração de cortisol sérico no cavalo crioulo colombianoAbstract Background: Cortisol is indicative of adaptation to physiological factors, disease and environmental stress in equines. Cortisol recently gained attention for its prognostic value in critical disease and as an indicator of fi tness and athletic performance. Objective: To determine baseline serum cortisol (SC) morning concentrations in the Colombian creole horse (CCH). Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Likewise, it was demonstrated that the increase in CORT in feces could be related to the decrease in the capacity of CORT binding in plasma and that this fact could be a component of these endocrine disorders in horses. However, other investigations in this species disagree [32,43,44].…”
Section: Agementioning
confidence: 61%
See 1 more Smart Citation
“…Likewise, it was demonstrated that the increase in CORT in feces could be related to the decrease in the capacity of CORT binding in plasma and that this fact could be a component of these endocrine disorders in horses. However, other investigations in this species disagree [32,43,44].…”
Section: Agementioning
confidence: 61%
“…On the other hand, it has been shown that high concentrations of CORT after exercise episodes can alter the anabolic responses of testosterone and growth hormone (GH) [79]. On the contrary, Zuluaga and Martínez [44] showed no significant differences in horse performance.…”
Section: Exercisementioning
confidence: 99%
“…Cupping therapy is contraindicated to be used over the regions that have injured flesh or dermis, abrasions, sunburns, and contusion; further, heavy and long cupping therapy is contraindicated to be used with the patients that are undertaking anticoagulants courses [ 5 ]. Cortisol concentration in equines has been used to determine stress generated by illness, pain, and lack of welfare [ 11 ]. Cortisol has gained interest due to its prognostic value in the critical phases and also as an indicator of fitness and athletic performance in sports horses [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol is a hormone secreted by the cortex of the adrenal glands and is a glucocorticoid with roles in such things as gluconeogenesis, proteolysis, lipolysis, hyperglycemia, and modulation of immunity and inflammation [ 10 , 12 ]. Likewise, it is considered the hormone of adaptation to different stress-generating activities in equines [ 3 , 9 , 13 ].…”
mentioning
confidence: 99%
“…The high variability in cortisol concentrations in horses and donkeys has led to the determination of reference values according to physiological status, age group, type of activity, management, and environmental conditions in different breeds around the world [ 5 , 11 , 13 ]. Despite extensive cortisol studies in equines and to a lesser extent donkeys, there is no information in mules.…”
mentioning
confidence: 99%